2012
DOI: 10.1097/mbc.0b013e32835029bf
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a point-of-care device in determining prothrombin time in an anticoagulation clinic

Abstract: New portable devices for the measurement of the prothrombin time and the international normalized ratio (INR) from capillary blood samples have demonstrated to have good correlation with classic laboratory methods in multiple clinical settings. In this study, we evaluated the performance of the point-of-care device CoaguChek XS (CoaguChek XS; Roche Diagnostics, Basel, Switzerland), comparing the INR results with the standard laboratory method (automatic coagulometer) in an outpatient anticoagulation clinic. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Based on a classical statistical approach used in comparative studies between POC devices and standard laboratory methods for the determination of INR, we found a similar correlation coefficient between methods in supra‐therapeutic INR, when compared to values obtained in within therapeutic range INR in a recent report that used the same methods . In our previous study, the same POC device was compared with an automated coagulometer (AMAX Destiny; DPC Medlab, Los Angeles, CA, USA) using a thromboplastin with an ISI of 1.15 (Simplastin Excel; BioMérieux, Durham, NC, USA), and the correlation coefficient in therapeutic and supra‐therapeutic INR range was 0.91 and 0.86, respectively.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on a classical statistical approach used in comparative studies between POC devices and standard laboratory methods for the determination of INR, we found a similar correlation coefficient between methods in supra‐therapeutic INR, when compared to values obtained in within therapeutic range INR in a recent report that used the same methods . In our previous study, the same POC device was compared with an automated coagulometer (AMAX Destiny; DPC Medlab, Los Angeles, CA, USA) using a thromboplastin with an ISI of 1.15 (Simplastin Excel; BioMérieux, Durham, NC, USA), and the correlation coefficient in therapeutic and supra‐therapeutic INR range was 0.91 and 0.86, respectively.…”
Section: Discussionmentioning
confidence: 61%
“…The use of POC tests for determination of the PT permits the release of an INR result in few minutes, without the need to collect whole blood samples, enabling optimization of patient anticoagulation monitoring. The accuracy and precision of this methodology have been demonstrated in different clinical scenarios in anticoagulated patients , so that this technology has been incorporated into several anticoagulation services. However, when thoroughly examining the studies that demonstrated the accuracy and precision of this methodology, one notes the paucity of data about assay performance in supra‐therapeutic INR .…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have compared the INR results obtained with POC devices versus conventional laboratory methods; however, most previously published studies have involved patients on oral anticoagulants for reasons other than a mechanical heart valve. Some have suggested that the difference between values acquired using these two methods might increase when INR values are greater than 3.5 .…”
Section: Discussionmentioning
confidence: 99%
“…POC INR testing is approved for VKA monitoring and can improve the time spent in the INR therapeutic range compared with the use of standard laboratory Prothrombin time/INR [ 30 ]. POCT for INR measurement can be as precise and accurate as laboratory testing [ 16 , 31 35 ], and can lead to comparable VKA-dosing decisions [ 33 , 35 , 36 ]. POC devices allow more convenient and frequent monitoring of anticoagulation therapy, inherently ensuring more patient education on anticoagulation management [ 37 ].…”
Section: Anticoagulation Therapy: Options and Managementmentioning
confidence: 99%